Perencanaan Persediaan Bahan Baku Produk Kursi Anyaman pada PT. Multi Kadera Sejati - Elsa Budi Ardhania; Erni Puspanantasari Putri (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
PT Multi Kadera Sejati is a company in the furniture industry that has always prioritised quality in the production of woven chairs. One of the problems that PT. Multi Kadera Sejati is a shortage of raw materials for woven chairs, apart from that, there is no optimal raw material inventory control system and they still use the conversion method, which results in the company experiencing production delays and hampers the delivery process to consumers, which can reduce consumers' confidence in ordering woven chairs from PT. Multi Kadera Sejati. The forecasting methods used in this research are Moving Average and Exponential Smoothing. In Material Requirement Planning (MRP), LFL and FPR lot-sizing techniques are considered to be able to solve this problem. The LFL method was chosen because it has the smallest results and the most optimal results. From the results of MRP calculations with LFL and FRP lot sizing, it was found that lowest cost for LFL was IDR 1,350,000